Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1145/3186894
|View full text |Cite
|
Sign up to set email alerts
|

Visually Augmented Audio-Tactile Graphics for Visually Impaired People

Abstract: Tactile graphics play an essential role in knowledge transfer for blind people. The tactile exploration of these graphics is often challenging because of the cognitive load caused by physiological constraints and their complexity. The coupling of physical tactile graphics with electronic devices offers to support the tactile exploration by auditory feedback. Often, these systems have strict constraints regarding their mobility or the process of coupling both components. Additionally, visually impaired people c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(18 citation statements)
references
References 44 publications
0
17
0
1
Order By: Relevance
“…Holloway et al (2018) conjecture that 3D printed maps reduce the cognitive load for map users by reducing the need for graphical tools that help illustrate an abstracted 2D landscape -such as side views or occlusion -allowing for a more 'purely' tactile experience; however, they note that it is unclear as to whether these benefits extend to maps specifically. 3D-printed touchplates that attach to tablet computers have been a popular research topic (Götzelmann, 2018;O'Modhrain et al, 2015), but the user experience has not been uniformly positive. Kane et al (2013) observed that users in their study were reluctant to learn how to operate a new device, although the users noted that it may be useful as a training device for people who have recently become B/ VI.…”
Section: Production: Multimodalitymentioning
confidence: 99%
See 1 more Smart Citation
“…Holloway et al (2018) conjecture that 3D printed maps reduce the cognitive load for map users by reducing the need for graphical tools that help illustrate an abstracted 2D landscape -such as side views or occlusion -allowing for a more 'purely' tactile experience; however, they note that it is unclear as to whether these benefits extend to maps specifically. 3D-printed touchplates that attach to tablet computers have been a popular research topic (Götzelmann, 2018;O'Modhrain et al, 2015), but the user experience has not been uniformly positive. Kane et al (2013) observed that users in their study were reluctant to learn how to operate a new device, although the users noted that it may be useful as a training device for people who have recently become B/ VI.…”
Section: Production: Multimodalitymentioning
confidence: 99%
“…That said, reading a tactile map is a much more cognitively intensive task than reading a visual map due to the need for constant referencing and orientation via touch (Ducasse et al, 2018;Perdue and Lobben, 2016), a task made even more difficult by the lack of a standardized symbol set. Digital tactile maps do have the capacity to reduce cognitive load by incorporating highfidelity media such as audio information (Bardot et al, 2016;Götzelmann, 2018), reducing the need to memorize symbols and labels, and so on. Digital tactile maps can also encourage exploration (Zeng and Weber, 2016) and facilitate learning to create further tactile media (Rassmus-Gröhn et al, 2007).…”
Section: Use and Evaluation: Access And Operationmentioning
confidence: 99%
“…These audiovisual tactile maps can be used in conjunction with tablets and smart phones. By integrating conductive elements into tactile maps printed in 3D, they can be recognized with a single touch on the screen of a mobile device, which facilitates the management of blind and partially sighted people 37 . Schools for the blind suffer from marginalization in terms of easy access and use of communication and assistive technology 38 .…”
Section: Modern Age and Mandatory Use Of Information Technology In Educationmentioning
confidence: 99%
“…Because touch and tactile (passive) interfaces are largely used by educators for VI students [28], research on TUIs for people with VIs has investigated different curricular fields. Tangible interfaces have been developed and evaluated to assist the exploration of diagrams [22], graphics [33], mathematics [2] and maps [6,20]. For instance, Ducasse and colleagues [17,18] developed a TUI to help people with VIs explore zoomable geographical maps.…”
Section: Related Work 21 Tangible Interaction For People With Vismentioning
confidence: 99%